Screening of Antioxidant Phenolic Compounds Produced by In Vitro Shoots of Brassica oleracea L. var. costata DC - Ferreres, Federico; Sousa, Carla; Pereira, David M.; Valentao, Patricia; Taveira, Marcos; Martins, Anabela; Pereira, Jose A.; Seabra, Rosa M.; Andrade, Paula B. (Combinatorial Chemistry & High Throughput Screening, 2009)
The phenolic compounds produced by in vitro shoots of Brassica oleracea L. var. costata DC were screened by HPLC-DAD-MS/MS. Thirty seven compounds were characterized, which included chlorogenic acids, flavonoids (the majority of them were hydroxycinnamic acid esters of kaempferol and quercetin glycosides) and hydroxycinnamic acyl glycosides (with predominance of synapoyl gentiobiosides). The antioxidant capacity of the shoots was assessed against DPPH radical and two reactive oxygen species (superoxide radical and hypochlorous acid). A strong concentrationdependent antioxidative capacity was verified in the DPPH and superoxide radicals assays, but a reduced effect was noticed against hypochlorous acid. The results obtained indicate that the in vitro production of B. oleracea var. costata shoots can become important in the obtention of a noticeable dietary source of compounds with health protective potential.
Keywords: phenolic compounds